ADMINISTRATIVE SYSTEM OF SELLING GOODS ON STORE COLLECTION NIKO USING MICROSOFT VISUAL FOXPRO 6.0 - Irawati Irawati; Hariyanto, Skom, MMSi Hariyanto, Skom, MMSi (Jurnal Sistem Informasi, 2003)
This computerized system is now used by many people as information that can assistin data processing. So also with the administrative system of selling goods at the dataprocessing store Niko is not maximal. For that created a computerized system inorder to facilitate the sale of goods.By using a computerized system expected error does not occur in a sale of goods. Sostore owners can estimate the gain or loss is derived.